An Audit of Requests for Fresh Frozen Plasma in a Tertiary Care Center in South India - Lingegowda, Jyothi B; Jeyakumar, Joshua Daniel; Muddegowda, Prakash H; Pitchai, R; Gopal, Niranjan; Sinha, Pammy (Journal of Laboratory Physicians, 2016)
Aim: To audit the fresh frozen plasma (FFP) usage with an insight into various guidelines.Materials and Methods: The blood bank records pertaining to FFP usage in patients admitted in our medical college hospital were retrospectively reviewed for 2 years for usage of FFP in various departments and evaluated for appropriateness of usage based on various guidelines, which included the 2013 guidelines published by the National Health and Medical Research Council and the Australasian Society for Blood Transfusion.Results: A total of 785 units of FFPs were transfused to 207 patients during the study period. The appropriate usage was found to be 59.3%, and the usage was most appropriate in massive transfusions.Conclusion: This study highlights the nonadherence to guidelines among clinicians which is mainly due to lack of knowledge of appropriate usage.
Keywords: Appropriate; audit; fresh frozen plasma